ANALISIS EFISIENSI TEKNIS PRODUKSI PADI SAWAH DI KABUPATEN PESISIR SELATAN - Dwiana Anisa Fitri; alpon satrianto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the effect of planting area, urea fertilizer, labor on rice production in Pesisir Selatan District. This type of research is a quantitative research that uses secondary data with panel data type, namely a combination of cross section data with 14 sub-districts in Pesisir Selatan Regency and time series data from 2013 to 2020, namely for 8 years. Data analysis techniques in this study using multiple linear regression analysis with panel data test and with stochastic frontier analysis (SFA). The results of the study concluded that planting area and labor had a positive and significant effect on rice production in Pesisir Selatan District. Urea fertilizer has a negative and insignificant effect on rice production in Pesisir Selatan District. The average level of technical efficiency of lowland rice in Pesisir Selatan Regency is 0.93 (93%), which means that the average rice production is said to be efficient because it is above 80%.